2009
DOI: 10.3122/jabfm.2009.01.080113
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vitamin B12 in Treating Recurrent Aphthous Stomatitis: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Vitamin B(12) treatment, which is simple, inexpensive, and low-risk, seems to be effective for patients suffering from RAS, regardless of the serum vitamin B(12) level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 24 publications
0
75
0
5
Order By: Relevance
“…In a randomized, double-blind, placebo-controlled test, a total of 58 patients were studied to determine the effect of 1,000 mcg of sublingual vitamin B 12 on aphthous ulcer outbreaks. 12 The authors found that "the duration of outbreaks, the number of ulcers, and the level of pain were reduced significantly (P>0.05) at 5 and 6 months of treatment." In addition, they found that 74% of the treatment group reached had no ulcers by the end of their 6-month observation period vs. 32% in the control group.…”
Section: Montelukastmentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled test, a total of 58 patients were studied to determine the effect of 1,000 mcg of sublingual vitamin B 12 on aphthous ulcer outbreaks. 12 The authors found that "the duration of outbreaks, the number of ulcers, and the level of pain were reduced significantly (P>0.05) at 5 and 6 months of treatment." In addition, they found that 74% of the treatment group reached had no ulcers by the end of their 6-month observation period vs. 32% in the control group.…”
Section: Montelukastmentioning
confidence: 99%
“…Ülkemizde yapılan diğer bir çalışmada RAS hastalarının %26,3'ünde vitamin B12, %25,4'ünde ise ferritin düzeyi düşüklüğü saptandığı bildirilmiştir 54 . Bu bilgilere ek olarak, yapılan bir çalışmada RAS hastalarına başlangıç vitamin B12 düzeyi ile bağımsız olarak verilen 1000 mcg vitamin B12'nin RAS rekürrens sıklığı, ülser sayısı ve ağrı şikayetinde belirgin düzelme sağladığı bildirilmiştir 55 . Çalışmamızda RAS ve hematinik eksiklikler arasındaki ilişkinin saptanması için hastaların demir, ferritin, vitamin B12, folik asit, hemoglobin ve hematokrit kan düzeyleri incelendi.…”
unclassified
“…1 As noted, this study suggests that daily 1000 mcg cyanocobalamin placed under the tongue may be preventive for recurrent aphthous stomatitis (RAS) after 5 months of use. Cyanocobalamin is not bioactive and must first be converted in the body to a bioactive form before it can be of benefit.…”
mentioning
confidence: 99%
“…To the Editor: I appreciated the information in this article, 1 as one who specializes in the diagnosis and treatment of attention deficit/hyperactivity disorder. I am curious whether the drug screen urinalysis performed in this case distinguished between amphetamines and methamphetamine; the article noted the patient's sample was positive for methamphetamine.…”
mentioning
confidence: 99%